An Aged Canid with Behavioral Deficits Exhibits Blood and Cerebrospinal Fluid Amyloid Beta Oligomers - Rusbridge, Clare; Salguero, Francisco J.; David, Monique Antoinette; Faller, Kiterie M. E.; Bras, Jose T.; Guerreiro, Rita J.; Richard-Londt, Angela C.; Grainger, Duncan; Head, Elizabeth; Brandner, Sebastian G. P.; Summers, Brian; Hardy, John; et al. (Frontiers in Aging Neuroscience, 2018)
Many of the molecular and pathological features associated with human Alzheimer disease (AD) are mirrored in the naturally occurring age-associated neuropathology in the canine species. In aged dogs with declining learned behaviour and memory the severity of cognitive dysfunction parallels the progressive build up and location of Aβ in the brain. The main aim of this work was to study the biological behaviour of soluble oligomers isolated from an aged dog with cognitive dysfunction through investigating their interaction with a human cell line and synthetic Aβ peptides. We report that soluble oligomers were specifically detected in the dog’s blood and cerebrospinal fluid via anti-oligomer- and anti-Aβ specific binders. Importantly, our results reveal the potent neurotoxic effects of the dog’s cerebrospinal fluid on cell viability and the seeding efficiency of the cerebrospinal fluid-borne soluble oligomers on the thermodynamic activity and the aggregation kinetics of synthetic human Aβ. The value of further characterising the naturally occurring Alzheimer-like neuropathology in dogs using genetic and molecular tools is discussed.